Index JCS - JCS Volume 2 (Department of Family and Consumer Sciences, Faculty of Social and Human Ecology, IPB University, 2017)
VOL 02 NO 01Adults Family Segment 21AEW 9Attitude 8behavior belief 8Comfortability 18Consumer Socialization 36Cost 18Farm Activiy 7FFQ 29Food Selection 32Friendly services 18GCEP 28HIPPC 42hybrid rice 4Information Exposure 31local farmers 35Location distance 18maternal age 35Motivation 45NHI 41Oryza sativa 3Parental Control 31Parental Modelling 30PBC 9Perception 44Popularity areas 18Segmentation 20Single Adults Segment 20SSA 41Subjective Norm 8Sukamandi 6Tour facilities 18Tour originality 18Tourism 15Typical Culinary Tour 22Vegetable Eating Habits 30Young Adult Segment 21 VOL 02 NO 02Adolescents 44buying behaviour 5Buying decision 9Claim 34Consumer education 44Consumer Education Materia 46Consumer Liability 47Consumer Rights 47FCQ 61Food Additives 35Food Label 29Frequency 8GCEP 61Halal logo 28Healthy Food Selection 62HRDA 60Inaplas 3Information Resources 48Interrelated Relationships Research 63IPS 45Label Reading 31MILOV 61NCPA 44NGO 31non-contagious diseases 36OTBA 17OTBA service 22Packaging Type 8Part Label Read 32perceptual instrument 4Place of Purchase 9psychological factor 65Reason Purchasing 9Research Sites 31Rural 8Sachet Packaging 6Spending 8SSS 44Transportation 17ULC 45Urban 8VMS 45